Structures of identification in Curriculum – European examples - Jobst, Solvejg; Trippestad, Tom Are (International Dialogues on Education Journal, 2015)
The educational debate in Europe is marked by the assumption that international education can help to cope with the increasing interconnectedness of people, activities, places and events. At the same time, the protection and restoration of each nation’s economic and cultural base against globalization and multiculturalism also have an impact on educational policies and educational practice. The characters of those competing discourses are strongly framed by structures of identification that imply various kinds of in- and out-group relations with different emotional, cognitive, and evaluative connotations. Against this background, the paper focuses on agencies that are being set up by educational policies and teachers in reshaping contemporary complex society. It investigates different European cases: a) European identification in the individual curriculum of German, Czech, and Polish teachers and b) identification as a political issue of nations outside the EU through a Norwegian example.